ANALISIS KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM PENYELESAIAN SENGKETA ANTARA NASABAH DENGAN BANK (STUDI PUTUSAN NOMOR: 218K/Pdt.Sus-BPSK/2019) - Kevin Hanif Nasution; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Consumer protection is often found in people's lives, of course in consumer protection there are business actors and consumers, in a healthy business there must be parties who are harmed in it and there are institutions that resolve disputes of the parties, namely BPSK, BPSK in carrying out their duties and authorities it is impossible to cross the line in the Consumer Protection Law Article 52, in the case that the author raised, the Supreme Court Judge decided that BPSK was not authorized to resolve banking consumer disputes and overturned the decision of the district court, this decision caused losses to consumers because consumers could not get their rights However, if you understand the contents of Article 52 BPSK has the authority to resolve any consumer disputes both in the goods and services sector and across sectors, as long as in terms of carrying out its duties and authorities it does not exceed what has been stipulated in the Law and in the future. Consumer protection laws that are now being updated with new ones so that in the future it does not cause confusion in the event of a dispute between business actors and consumers.